Modelling subject-specific patellofemoral joint dynamics - Muller, Jacobus Hendrik (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.